Analisis Yuridis Putusan Peradilan Tata Usaha Negara Tentang Pencabutan Gugatan Sengketa Kepegawaian: (Studi Perkara Nomor 38/G/2020/PTUN.SMG) - Tarasari, Binar; Kusnady, Rae Jonathan; Septiningsih, Ismawati (Universitas Kapuas, 2024)
Withdrawal of a lawsuit is one of the legal problems encountered in the judicial process. This research aims to analyze Decree Number 38/G/2020/PTUN.SMG concerning decisions regarding the withdrawal of lawsuits by analyzing the suitability of the decision to the law and its legal consequences. This research aims better to understand the compatibility of decision Number 38/G/2020/PTUN.SMG with Law Number 5 of 1986 and to research and find out about the legal consequences that arise for both parties after the lawsuit's withdrawal. Number 38/G/2020/PTUN.SMG. This research is normative legal research with a statute approach and a case study approach. The summary of the research results is that Decision Number 38/G/2020/PTUN.SMG is by applicable legislation and there are legal consequences of withdrawing the lawsuit, namely the end of the case, the parties return to their original state, and the court costs are charged to the plaintiff.